2022
DOI: 10.1080/01942638.2022.2138733
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the French European Little Developmental Coordination Disorder Questionnaire (LDCDQ-FE): A Pilot Study

Abstract: Aims. The Little Developmental Coordination Disorder Questionnaire (LDCDQ) is a parental questionnaire designed to identify preschool children at risk of Developmental Coordination Disorder (DCD). This study aimed to translate and cross-culturally adapt the LDCDQ for French European informants (Little Developmental Coordination Disorder Questionnaire -French European [LDCDQ-FE]) and to undertake a pilot examination of its psychometric properties on a French sample. Methods. A thorough process of cultural adapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The Little Developmental Coordination Disorder Questionnaire-French European (LDCDQ-FE)24 25 and for children over 7 years of age, the Developmental Coordination Disorder Questionnaire-French European (DCDQ-FE)26 assess DCD. Scales include 15 items grouped into three domains: control during movement, fine motor function and writing, and global coordination.…”
Section: Methodsmentioning
confidence: 99%
“…The Little Developmental Coordination Disorder Questionnaire-French European (LDCDQ-FE)24 25 and for children over 7 years of age, the Developmental Coordination Disorder Questionnaire-French European (DCDQ-FE)26 assess DCD. Scales include 15 items grouped into three domains: control during movement, fine motor function and writing, and global coordination.…”
Section: Methodsmentioning
confidence: 99%
“…As a downward extension of the DCDQ'07, the Little Developmental Coordination Disorder Questionnaire (LDCDQ) was originally developed in Hebrew to identify motor development and coordination difficulties of young preschoolers aged 3-and 4-years (Rihtman et al, 2011). The original LDCDQ demonstrated sound psychometric properties (Rihtman et al, 2011), and since its initial publication, the LDCDQ has been adapted for use in multiple countries including -among others -the Netherlands (Cantell et al, 2018), South Africa (Venter et al, 2015), France (Jover et al, 2013), and Canada (Wilson et al, 2015). These studies have demonstrated the need for a variety of culture-and context-specific amendments, including adjustment of item phrasing and detail, the inclusion of alternate item examples, age-range extension to include 5-year-old children (where children begin schooling later), and the adoption of alternate sub-scores structures.…”
Section: Introductionmentioning
confidence: 99%